(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Cerebral venous sinus thrombosis (CVST) is one of the most serious and fatal disorder of intracranial venous pathways characterized by clot formation in Cerebral venous sinuses. Generally, CVST is a fulminating process with a high rate of mortality (1 in 3 patient) secondary to a spreading bacterial infection specially over head and neck region where coagulase positive Staphylococcus (90%) is mostly responsible. Individuals with hypercoagulable state i.e., pregnancy or puerperium and malignancy can also suffer from this form of thrombosis. Here we are presenting such a case, who developed CVST on the 5th day of puerperium with features of persistent headache and eye problems. The diagnosis was confirmed with MRI in combination with Magnetic resonance venography (MRV). She responded well to low molecular weight heparin (LMWH) and was discharged on long term oral anticoagulant and regular follow-ups. Her subsequent pregnancy was uneventful without repeat attack of CVST. J Bangladesh Coll Phys Surg 2024; 42: 82-85